Adoption of Cocoa Rehabilitation Techniques among Cocoa Farmers in Oyo State, Nigeria. - Ayodele, Omowunmi Veronica; Afuye, Itunu Esther (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
The study assessed the adoption of cocoa rehabilitation techniques (CRTs) by cocoa producers in Ido and Oluyole Local Government Areas Oyo State, Nigeria. Respondents for the study were 97, chosen through a multi-stage sampling technique. T-test, mean statistics, and percentages were used for data analysis. The study’s findings showed the mean age of cocoa farmers to be 55 years and the mean for farming experience was 20.9 years. It further revealed, that though there was a low adoption of cocoa rehabilitation techniques (x ̅=1.72), there was a significant difference in the annual output of cocoa before (x ̅=211.83kg) and after (x ̅=605.24kg) adoption of cocoa rehabilitation techniques with a p-value= 0.021.The most used techniques were planting cocoa under trees (x ̅=3.63) and complete replacement of old cocoa farms (x ̅=2.10). It also revealed scarcity of improved cocoa varieties (x ̅=4.70) and inadequate capital (x ̅=4.62) were the major constraints to cocoa rehabilitation. It was therefore recommended that cocoa rehabilitation efforts should be intensified while ensuring adequate availability of improved cocoa varieties and capital for the acquisition of necessary inputs.